Modeling the segment interactions of Ukraine’s financial market - Liudmyla Prymostka; Іryna Krasnova; Ganna Kulish; Andrii Nikitin; Valentyna Shevaldina (Investment Management & Financial Innovations, 2020)
This study is devoted to assessing the level of individual segments interconnectedness within the financial market of Ukraine (FMU) and their dynamics in uncertain conditions. The methodology of the systematic approach is used to investigate the dynamic relationship between individual segments of the financial market of Ukraine, namely credit (deposit-credit) market, stock market (market of securities), government securities market, currency market, and interbank market. The study of financial market dynamics focuses on the description of the price indicators of individual market segments, which are monitored using time series analysis and statistical methods. The results of the time series assessment revealed the fractal characteristics of the Ukrainian financial market as a measure of sustainability (namely inertia). It is revealed that all segments of the financial market, except credit, are characterized by persistence. It is established that the development of market segments is uneven and is characterized as bifurcation. The credit segment is addicted to insider behavior and has the highest risk concentration. It is revealed that the foreign exchange market is still in crisis. The results of modeling the correlation relationships between market segments have shown that, in the presence of such relationships, they differ in the strength and nature of the interaction. They are volatile, unstable, and situational, dependent on external conditions. The credit market has a relationship with other segments, not significantly strong but stable. The results of the analysis indicate the dynamic development of segments within the Ukrainian financial market in the presence of interconnections between them. AcknowledgmentThe study was conducted within the framework of the State Budget of the Kyiv National Economic University named after Vadym Hetman on the topic “Innovative development of banking activities in the integrated financial environment” (state registration number 0117U001178).